Inverse opal-structured all-in-one water purification filter designed for the effective removal of multi-pollutants. (April 2023) - Kim, Hee Jung; Han, Gill Sang; Kim, Jaesung; Kim, Young Ju; Choi, Jin Hyuk; Lee, Jae Myeong; Yoon, Geon Woo; Lee, Hongshin; Cho, In Sun; Lee, Jaesang; Jung, Hyun Suk
Abstract: Despite the dominance of centralized water treatment systems in the past decades, there is increased demand for instant water treatment in isolated areas, i.e., decentralized water treatment. Moreover, as wastewater contains multiple pollutants such as heavy metals, anionic substances, and organic matter, research on their simultaneous removal is one of the most significant issues for practical application. In this study, we reported a novel all-in-one multi-pollutants removal filter based on inverse opal (IO) structures for decentralized water treatment. This IO-based all-in-one filter consists of three adsorbents: Fe2 O3, NiOx, and S-doped graphene, for the simultaneous removal of heavy metals, anionic substances, and organic matter. The filter was particularly designed to enhance the water flux of nano-absorbents with high absorption capacity under a water-flow system. As a result, the all-in-one multi-pollutants removal filter exhibited excellent adsorption performance (phenol: 108.16 mg/g; Zn: 209.26 mg/g; and phosphate: 202.54 mg/g) at ultrafast water flux (1167 L/m 2 ·h). We successfully designed an efficient multi-pollutants removal system considering the removal mechanisms suitable for different pollutants, the correlation of pollutants, and the water flow by IO structure. Moreover, our results demonstrated the simultaneous removal of multi-pollutants from wastewater using a single-unit purification system, which would provide great significance to decentralized water purification systems. Graphical abstract: Unlabelled Image Highlights: The IO-based filter comprises three adsorbents, including S-G, Fe2 O3, and NiOx . Three adsorbents remove heavy metal, organic, and anionic pollutants, respectively. The IO-base filter was designed to optimize the flux and adsorption performance. IO-based filters showed excellent performance in multi-pollutants removal.